The «Essence of Christianity» in the Beginnings: A Reflection - Guijarro Oporto, Santiago (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2021)
The present essay interrogates the New Testament about what constitutes the «essence of Christianity». It begins by noting the centrality of Jesus Christ, whom his first followers regarded as the foundation and cornerstone. It then notes that the Easter confessions on which this conviction is rooted not only say something about Jesus, but also affirm something about God, whose image is modified by the confession of Jesus as Son and Lord. As a consequence, the new image of God appears as the most distinctive feature of Christianity in the beginning.